Negative Regulation of BRCA1 Gene Expression by HMGA1 Proteins Accounts for the Reduced BRCA1 Protein Levels in Sporadic Breast Carcinoma - Baldassarre, Gustavo (American Society for Microbiology, 2003)
A drastic reduction in BRCA1 gene expression is a characteristic feature of aggressive sporadic breast carcinoma. However, the mechanisms underlying BRCA1 downregulation in breast cancer are not well understood. Here we report that both in vitro and in vivo HMGA1b protein binds to and inhibits the activity of both human and mouse BRCA1 promoters. Consistently, murine embryonic stem (ES) cells with the Hmga1 gene deleted display higher Brca1 mRNA and protein levels than do wild-type ES cells. Stable transfection of MCF-7 cells with the HMGA1b cDNA results in a decrease of BRCA1 gene expression and in a lack of BRCA1 induction after estrogen treatment. Finally, we found an inverse correlation between HMGA1 and BRCA1 mRNA and protein expression in human mammary carcinoma cell lines and tissues. These data indicate that HMGA1 proteins are involved in transcriptional regulation of the BRCA1 gene, and their overexpression may have a role in BRCA1 downregulation observed in aggressive mammary carcinomas.